2020
DOI: 10.1111/tbed.13609
|View full text |Cite
|
Sign up to set email alerts
|

Babesia vogeli in dogs in Chile

Abstract: Parasites of the genus Babesia are apicomplexan protozoa of the order Piroplasmida, which parasitize erythrocytes of wild and domestic birds and mammals (Alvarado-Rybak, Solano-Gallego, & Millán, 2016; Penzhorn, 2006). These parasites can cause a wide spectrum of clinical signs, from subclinical signs to intense fever, haemolytic anaemia, splenomegaly and even death (Greene, 2012). The principal species capable of causing pathology in canines are Babesia canis, B. rossi, B. gibsoni and B. vogeli. Their transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…DNA was not detected during this survey. Babesia vogeli was recently found in Chile [36], is surprising we had not found it despite been present the competent vector R. sanguineus. Absent of Hepatozoon spp.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…DNA was not detected during this survey. Babesia vogeli was recently found in Chile [36], is surprising we had not found it despite been present the competent vector R. sanguineus. Absent of Hepatozoon spp.…”
Section: Discussionmentioning
confidence: 49%
“…Canine babesiosis in South America is caused by the intraerythrocytic protozoan parasites Babesia vogeli and Babesia gibsoni [34,35]. Recently, B. vogeli has been reported in Chile [36]. Dog population in Chile was estimated at 4.059.200 individuals [37], and owned free-roaming dogs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…All the sequences analyzed in this study were consistent with Babesia vogeli. In general, this has been the most frequently detected species in dogs in Brazil (Passos et al, 2005;Duarte et al, 2011;O'Dwyer et al, 2009;Spolidorio et al, 2011;Lemos et al, 2012, Moraes et al, 2015, Sousa et al, 2017Barbosa et al 2020, Castro et al, 2020 and also others countries as China, Sudan, Spain, Venezuela, Chile, and USA (Li et al, 2020;Oyamada et al, 2005;Criado-Fornelio et al, 2007;Di Cataldo et al, 2020;Rey-Valeiron et al, 2007;Passos et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The molecular analyses of the present study only identified B. vogeli. In fact, B. vogeli is the piroplasmid species that has been most detected in dogs in different regions of Brazil [16,18,25,28,[30][31][32][35][36][37], and in other countries [37][38][39][40][41][42]. However, in addition to this species, the piroplasmid R. vitalii has also been detected in dogs in the southern region of Brazil and in municipalities in the mountain region of the state of Rio de Janeiro, by means of molecular tools [13,14,16].…”
Section: Discussionmentioning
confidence: 99%